Innovation and patents as a business success factor - Youseline Garavito Hernández; Javier Francisco Rueda Galvis (Journal of Economics, Finance and Administrative Science, 2021)
Purpose - The purpose of this paper is to expose the impact of innovation and patent registration, as a strategy that contributes to business success in the current competitive and globalized market conditions. Design/methodology/approach - This paper presents a study on the innovation and contribution of the patent registry in the growth of economic sales of 1,746 companies in the Colombian manufacturing sector, whose applied methodology was a statistical correlation analysis and a binary logistic regression. Findings - The results reveal a positive relationship among incremental product innovations with the achievement of sales success, although it is evident that patent registration negatively influences business success as a factor in innovation. Originality/value - This study allows organizations to understand the importance of developing innovation processes and patent registration as a competitive factor that drives sales growth and success.
Keywords: 330; Business success; Innovation; Patent registration; Sales growth